Complexity and public policy a new approach to twenty-first century politics, policy and society - Geyer, Robert (London Routledge, 2010)
This book provides a clear, concise and readable introduction to complexity thinking, its application to the social sciences and public policy, and the relevance of some of its various tools to those fields of politics, health, the international realm, development, planning and terrorism.
Includes bibliographical references (p. [199]-210) and index.
Keywords: Policy sciences